The impact of parental attitudes toward children with primary headaches. (October 2019) - Ertem, Devrimsel Harika; Bingol, Ayhan; Ugurcan, Busra; Mercan, Özlem; Simsek, Ismail; Sağlam, Hanife; Ozge, Aynur; Uluduz, Derya
There is a lack of data on parental attitudes toward children with primary headaches. The aim of this study is to determine whether there is a relationship between primary headaches and parental attitudes in the pre-adolescent pediatric population. In this cross-sectional study, 195 children with primary headache and 43 healthy children aged 9–16 years were included. A questionnaire for sociodemographic variables, visual analog scale (VAS), Social Anxiety Scale and Depression Inventory for Adolescents and Children, and Parental Attitudes Determining Scale (PATS), which is an attitude measure specifically designed to evaluate psychological adjustment, were administered. Of 195 children (female/male ratio: 89/106, mean age: 12.59 ± 1.09 years), episodic migraine ( n = 90), chronic migraine ( n = 25), and tension-type headache ( n = 80) were evaluated. There was no significant difference among headache groups and healthy subjects in terms of depression, anxiety, and fathers' attitude scale scores. However, there were significant differences in mean mothers' attitude scale scores and VAS scores ( p = .002, p = .000). Mean oppressive-authoritarian attitude subscale scores of mothers' was significantly higher in children with chronic migraine ( p = .000). A relationship between depression and VAS scores among all patient groups was detected ( p = .000). Parental age was negatively related to PATS scores of children with episodic migraine and tension-type headache ( p = .037 and p = .036). Parental attitudes may elevate psychiatric symptoms and influence children's perception of pain intensity and result in chronification of headache. Our findings support that mothers' attitude toward children with chronic migraine has strong impacts on the child's pain experience.